Literature Review and Experiment: Diversity of Bacteria in Forest, Revegetated Post-Mining Land, and Active Tin Mining with A Metagenomic Approach - Eka Sari; Andhika Puspito Nugroho; Endah Retnaningrum; Irfan Dwidya Prijambada (Universitas Pendidikan Indonesia, 2023)
The objective of this study was to investigate the diversity of bacteria in the rhizosphere of Acacia grow in the forest and different ages of revegetated land and non-rhizospheric bacteria from active tin mining soil on Bangka Island with a metagenomic approach and to investigate its relationship with physicochemical properties of the soil and its metal content. 17 species/genera were found in the four fields, and Bradyrhizobium is the dominant genus. Bacterial communities of the forest (more than 5 years in revegetated post-tin mining land containing C, N, P, and Fe) are Paraburkholderia sp., Bacillus sp., Candidatus-Xiphinematobacter, and Bacterium enrichment. The physicochemical properties of soil from less than 5 years of revegetated contain Cu, Cr, and Mo, and the dominant species in this soil were Bulkhorderia sp., Bacillus lehensis, B. fordii, B. thermolactis, Chloroflexi bacterium, and Thermonosporaceae bacterium. The physicochemical properties of soil from the mining were dominated by Cd and Ni, and the dominant species in this soil were Sinomonas atrocyanea.